Employers' search and the efficiency of matching - Michele Pellizzari (Institute for the Study of Labor (IZA), 2005)
Unskilled workers in low productivity jobs typically experience higher labour turnover. This paper shows how this empirical finding is related to variation in the efficiency of the matching process across occupations. A simple theoretical model of employers' search shows that firms find it optimal to invest relatively little in advertisement and screening when recruiting for low productivity jobs. This generates more separations and higher turnover at the bottom than at the top of the jobs' distribution. The analysis of a unique sample of British hirings, containing detailed information about employers' recruitment practices, shows that more intensive recruitment leads to matches of better quality that pay higher wages, last longer and make employers more satisfied with the person taken on.
Keywords: J63; J64; M51; 330; labour turnover; matching; recruitment; hiring